The combustible mix of coalitional and discursive power: British trade unions, social media and the People's Assembly Against Austerity. (9th March 2022) - Geelan, Torsten
Abstract: This article investigates how the British trade union movement sought to challenge the politics of austerity after the North Atlantic financial crisis of 2008 by founding a union‐led coalition: the People's Assembly Against Austerity. To lay the ground for the study, it redefines the concept of discursive power as the capacity of trade unions to influence the public debate by producing and self‐mediating frames and circulating them through the mainstream media, the Internet and social media to a mass audience. Data were collected over 3 years (2013–2015) using interviews and scraping tweets from Twitter. The findings reveal how the People's Assembly created and sustained a heterogenous coalition through a policy of nonpartisanship and a consensus‐driven decentralised network of grassroots local assemblies orchestrated by a national organisation. The article contributes to the literature on trade union revitalisation by demonstrating how combining coalitional and discursive power is a combustible mix that can help revitalise the political influence of trade unions.